Urban sustainability – a segmentation study of Greater Brisbane, Australia. Issue 3 (3rd March 2016) - Muriuki, Grace; Dowd, Anne-Maree; Ashworth, Peta
Abstract : Setting universal goals for sustainability is problematic and may hinder the adoption of sustainable pathways as different sectors of society often have differing opinions on not just what sustainability means for them, but also what is of priority to them. This paper tests a set of psychographic, behavioural, lifestyle and social identities to segment the public on sustainability. We evaluate general knowledge, apply social-choice tools to identify public priorities, and then apply segmentation to reveal broad strata of community profiles around these choices. We discuss our findings in the context of moving beyond knowledge on sustainability and general public choices, to more nuanced messaging and engagement that respects differences in sustainability orientations. We suggest that by focusing on what matters most for different segments of society, there is potential to design effective processes to engage with people and acquire better ownership of sustainability.